1997
DOI: 10.1128/mcb.17.10.5784
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Mediates Epidermal Growth Factor-Induced Activation of the c-Jun N-Terminal Kinase Signaling Pathway

Abstract: The signaling events which mediate activation of c-Jun N-terminal kinase (JNK) are not yet well characterized. To broaden our understanding of upstream mediators which link extracellular signals to the JNK pathway, we investigated the role of phosphatidylinositol (PI) 3-kinase in epidermal growth factor (EGF)-mediated JNK activation. In this report we demonstrate that a dominant negative form of PI 3-kinase as well as the inhibitor wortmannin blocks EGF-induced JNK activation dramatically. However, wortmannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 49 publications
8
105
0
Order By: Relevance
“…It has been reported that PDGFR activates JNK/ SAPK through the PI-3 kinase pathway (LopezIlasacca et al, 1997), whereas this pathway is not implicated in JNK/SAPK activation induced by TNFa, UV irradiation or osmotic shock (Logan et al, 1997). In our studies, PI-3 kinase seems to be a negative regulator of JNK/SAPK activation by T/P since the PI-3 kinase inhibitor LY294002 does not inhibit T/Pinduced JNK/SAPK activation, but on the contrary, potentiates this activation and increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PDGFR activates JNK/ SAPK through the PI-3 kinase pathway (LopezIlasacca et al, 1997), whereas this pathway is not implicated in JNK/SAPK activation induced by TNFa, UV irradiation or osmotic shock (Logan et al, 1997). In our studies, PI-3 kinase seems to be a negative regulator of JNK/SAPK activation by T/P since the PI-3 kinase inhibitor LY294002 does not inhibit T/Pinduced JNK/SAPK activation, but on the contrary, potentiates this activation and increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the signalling pathways through which these growth factors and oncogenes activate JNK/SAPK pathway are still unde®ned. Recently, it has been reported that a dominant negative form of PI-3 kinase as well as PI-3 kinase inhibitors block EGF-induced JNK/SAPK activation, although these inhibitors had no e ect on JNK/SAPK activation induced by UV irradiation, osmotic shock, or TNFa (Logan et al, 1997). Furthermore, both PI-3 kinase and JNK/SAPK pathway activation has been shown to be involved in the transforming potential of the human leukaemia oncogene, BCR/ABL (Skorski et al, 1997;Raitano et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, PI3 kinase has been described to mediate Ret e ects on cytoskeleton (van Weering and Bos, 1997) and it acts upstream Rho-related GTPases in the case of PDGFR signalling (Hawkins et al, 1995). Moreover, both in the case of epidermal growth factor receptor (Logan et al, 1997) and of Met (Rodrigues et al, 1997), PI3 kinase has been demonstrated to be important for JNK activation. Whether this is also true for Ret remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Several growth factors have been shown to activate the c-Jun terminal kinase (JNK), through PI3K (Logan et al, 1997;Minden and Karin, 1997;Minden et al, 1995). To determine whether JNK is activated by Gas6-dependent survival signalling, JNK activity was measured at various times after induction of cell death and Gas6 addition.…”
Section: Gas6-dependent Downstream Survival Signalling In Nih3t3 Cellsmentioning
confidence: 99%
“…In fact Rac and Cdc42 in their active form bind and activate Pak; dominant negative Pak suppresses interleukin 1, UV and growth factor induced JNK and p38 activation (Zhang et al, 1995). Growth factors such as EGF have been shown to activate the JNK pathway through PI3K (Logan et al, 1997). Overexpression of PI3K catalytic subunit (p110) can lead to Rac activation (Klippel et al, 1996;Minden et al, 1995;Minden and Karin, 1997) and its expression in COS cells was shown to induce activation of JNK (Rei et al, 1996).…”
Section: Introductionmentioning
confidence: 99%